ROAD SAFETY PERCEPTION TOWARDS SUSTAINABLE TRANSPORT (A CASE OF ROAD SAFETY PROGRAMS IN YOGYAKARTA, INDONESIA) - Nurhidayati, Zuni Asih; Sebhatu, Samuel Petros; Malkamah, Siti (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The Aims of this study is suggests a set of scheme on road safety policy improvement in Yogyakarta by firstly understanding the road user perception on current road safety programmes related to the ongoing problems, then analyse it along with other actor’s role in achieving sustainable transport. “The Five Pillars” as current road safety action plan are followed to actualize safe mobility and “zero accident”. Using Yogyakarta as a case study within the Research Design, this qualitative study are conducting triangulation technique in data collection. The Study Empirically describe the present situation and gain the road user perception by marriage with The Theory of Planned Behaviour, Sustainability, Value Creation and Hongkong’s Transport Policy in theoretical part. It indicates according the Results, there still existed a gap of perception between road users and road safety officer due to the existence of irregularities within the road safety programs implementation.